Direct fermentation of sugar cane syrup to ethanol - Lee, Shee Yen (Universiti Malaysia Sarawak (UNIMAS), 2013)
Ethanol production from pure sugar cane syrup (SCS) were carried out to compare the efficiency of batch fermentation with commercial glucose using Saccharomyces cerevisiae baker’s yeast and Saccharomyces cerevisiae CSI-1 (JCM 15097). Fermentation of Baker’s yeast and CSI-1 in SCS medium supplemented with 0.5% (w/v) of yeast extract at 37oC, initial pH adjusted to 5.5, agitation 200 rpm, produced high concentration of ethanol in 1.5L lab scale fermentor. Ethanol production by dry Bakers’s reached 138g/L and yield 156.9% of theoretical yield. For CSI-1, a maximal concentration of 73.3g/L and a yield of 88.9% of theoretical yield were obtained from fresh SCS. The result from this research demonstrate that in Malaysia, sugar cane syrup could be employed as an alternative renewable carbon source for ethanol production using batch fermentation with Saccaharomyces cerivisiae.